2023
DOI: 10.3390/catal13050894
|View full text |Cite
|
Sign up to set email alerts
|

NO Oxidation on Lanthanum-Doped Ceria Nanoparticles with Controlled Morphology

Abstract: The present work aims to assess the impact of morphology and reducibility on lanthanum-doped ceria nanocatalysts with controlled morphology on the NO oxidation reaction. Specifically, samples were prepared using a hydrothermal method incorporating lanthanum at varying molar concentrations (0, 5, 10, and 15 mol.%) into ceria with a controlled morphology (nanocubes and nanorods). The structural, compositional, and redox characterization of these catalysts has been performed via scanning transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This results in the formation of Ce–La oxides solid solution without altering the face-centered cubic crystal structure of CeO 2 . It is also noteworthy that the Ce-La21- x samples show an overall shift toward lower diffraction angles, a phenomenon attributed to the incorporation of La into the crystal structure, resulting in increased crystal spacing . Furthermore, increasing the pH of the complexing-precipitation process by using NH 3 ·H 2 O leads to weaker and less defined XRD diffraction peaks.…”
Section: Resultsmentioning
confidence: 97%
“…This results in the formation of Ce–La oxides solid solution without altering the face-centered cubic crystal structure of CeO 2 . It is also noteworthy that the Ce-La21- x samples show an overall shift toward lower diffraction angles, a phenomenon attributed to the incorporation of La into the crystal structure, resulting in increased crystal spacing . Furthermore, increasing the pH of the complexing-precipitation process by using NH 3 ·H 2 O leads to weaker and less defined XRD diffraction peaks.…”
Section: Resultsmentioning
confidence: 97%
“…At the same time, A. García-García et al also modified the Ce/spinel-based lean NO x -trapping (LNT) compositions with and without Ba with MnO x by initial wet impregnation. [45] By studying the effect of adding MnO x to the LNT composition based on MgAl 2 O 4 /CeO 2 at the adsorption temperature of 300 °C on the NO x storage/release performance, it can be found that the formation of MnO x layer on the spinel/ CeO 2 mixture can beneficially inhibit the formation of BaAl 2 O 4 and facilitate the formation of BaMnO 3 . In contrast to the previous study, the presence of Ba can inhibit the oxidation activity of NO, but this perovskite phase containing manganese (IV) has been shown to be very effective for NO x storage even at low NO 2 /NO ratios, which will also facilitate the catalytic process of soot oxidation.…”
Section: Other Structuresmentioning
confidence: 99%